Addressing Research Fatigue in Energy Communities: New Tools to Prepare Researchers for Better Community Engagement. Issue 3 (4th March 2021) - Taylor, Suzi; Bills Walsh, Kathryn; Theodori, Gene L.; Jacquet, Jeffrey; Kroepsch, Adrianne; Haggerty, Julia H.
Abstract: Two innovative educational products aimed at improving the quality of human-subjects research in and around energy-impacted communities are introduced here. The educational materials include: (1) a self-paced online education course titled "Understanding and Addressing Research Fatigue in Rural Communities" and (2) an accompanying workbook for research planning titled "Engaging in Energy Communities: The Role of the Researcher." We explain how two recent studies were instrumental in identifying the need for the online education course and the associated workbook. We conclude the paper with guidance on how to access these new resources, which we believe will be particularly useful for graduate students and early-career researchers. We invite feedback from users as well as from colleagues who may wish to use these educational materials.